A study on consumer’s acceptance towards green banking practices / Nurul Aien Abd Aziz...[et al.] - Abd Aziz, Nurul Aien; Musa, Mohd Hafizan; Mohamad Khalid, Rusnani; Abd Aziz, Noreen Noor (UiTM Cawangan Johor, 2019)
Presently, green practice has become a massive trend in the global banking sector. The concept of green banking has caused the banking industry to introduce paperless concept for its operations and technology adoptions across the country, as an effort to support the go green concept. This concept is also an alternative for the banking industry to reduce the cost of operations while increasing the banking operation productivity. It is very important for the banking industry to fully understand the acceptance of green banking practices among its customers, because this will influence the customers’ decisions for fractional banking activities like deposits, credit activities, and investments. The acceptance of customers towards the initiatives of green banking will contribute in enhancing the operation and performance of the banking sector in Malaysia. The main objective of this study is to investigate the determinant contributing to the acceptance of green banking among the customers. This study was conducted in Johor, and it used the simple random sampling. The sample was comprised of 118 respondents who participated in answering the given questionnaires. For the findings, the perceived usefulness and safety were the predictors of the acceptance of green banking practices among the customers.